AI-enabled agile Internet of things for sustainable FinTech ecosystems - Kautish, Sandeep 1981-; Kaur, Guneet 1994- (IGI Global, 2022)
"This book presents the advances in AI-assisted agile IoT for fintech, helping readers to reveal new applications, current issues, challenges and future directions in the field of AI-assisted agile IoT for fintech applications and ecosystems.
Includes bibliographical references and index. - Mode of access: World Wide Web
Keywords: Finance -- Data processing; Financial services industry -- Technological innovations; Artificial intelligence -- Financial applications